Comparison of the constraint parameters in elastic-plastic fracture mechanics (Fracture and Structural Integrity, 2019)
To describe the effect of crack-tip constraint on the stress field for finite cracked bodies, the following most widely used constraint parameters can be employed in elastic-plastic fracture mechanics, namely, local triaxiality parameter, constraint parameter Q, the second fracture mechanics parameter A using a three-term elastic-plastic asymptotic expansion. To establish the relationship between different constraint parameters, the crack-tip stress fields are employed. Relationship between the crack-tip constraint parameters A, A2, Q and of elastic-plastic fracture mechanics is investigated.
Keywords: Constraint parameters; Elastic-plastic fracture mechanics